Evaluation of four plant species for phytoremediation of copper contaminated soil - Ahmadpour, Parisa; Ahmadpour, Fatemeh; Sadeghi, SeyedMousa; Tayefeh, Farhad Hosseini; Soleimani, Mohsen; Abdu, Arifin (Academic Press, 2015)
Copper (Cu) is known as the most dangerous pollutant, particularly at higher concentrations. Four forest species, namely, Jatropha curcas, Acacia mangium, Dyera costulata and Hopea odorata were used. Randomized complete block design (RCBD) with four replications was used in a factorial arrangement. The aim of this study was to assess the phytoremediation potential of the tested species for Cu-contaminated soil. Copper sulphate (CuSO4•5H2O) was used as a source of Cu. The different levels of Cu were (Cu0 = control, Cu1 = 50, Cu2 = 100, Cu3 = 200, Cu4 = 300 and Cu5 = 400 mg kg−1). The pots were filled with growth media, and the seedlings were transplanted. The parameters monitored and analyzed were soil physio-chemical properties, growth variables, plant dry biomass and heavy metal concentrations. Higher Cu levels significantly decreased (p ≤ 0.05) the growth performance and the production of dry biomass. Total Cu concentration in tested species increased significantly (p ≤ 0. 05) with an increase in the Cu level. J. curcas attained the highest Cu removals within each level of Cu. The BCFs of Cu were > 1 within each level of Cu and in control media. Plant species grown in the media treated with various levels of Cu exhibited very small TFs (< 1). The highest total Cu concentration and the maximum Cu removal efficiency among plant species were observed in J. curcas. In addition, most parts of Cu accumulated in the roots of the four tested species. As a conclusion, J. curcas was the most effective species for phytoremediation of Cu-contaminated soils through phytostabilization.